Study of Product Quality, Customer Experience and Perception of Price Accuracy in Increasing Repurchase Interest in Scarlett Products in West Kalimantan - Irmayanti, Dian; Kristianto, Aloysius Hari (ProBisnis : Jurnal Manajemen, 2024)
This research was conducted with the intention of determining the influence of product quality, customer experience and perceived price suitability on repurchase interest in Scarlett skin care products. The sampling technique in this research used a purposive sampling technique which was chosen because the researcher used his own judgment in selecting members of the population who were deemed able to provide information. The number of samples used in this research was 148 respondents. The results of the research were collected through questionnaires which were processed and analyzed using multiple regression analysis. The data quality test in this research is the validity test, reliability test using Cronbach Alpha. To test the classical assumption, use the normality test and multicollinearity test. To test the hypothesis, use multiple linear regression, t test, goodness of fit test (f test) and coefficient of determination (R2 test ) . The results of this research show that product quality, customer experience and perceived price suitability have a positive and significant effect on repurchase interest in Scarlett skin care products.